Heat transfer and entropy generation for laminar forced convection flow of graphene nanoplatelets nanofluids in a horizontal tube. (August 2015) - Mehrali, Mohammad; Sadeghinezhad, Emad; Rosen, Marc A.; Akhiani, Amir Reza; Tahan Latibari, Sara; Mehrali, Mehdi; Metselaar, Hendrik Simon Cornelis
Abstract: The results are reported of an investigation of the heat transfer characteristics and entropy generation for a graphene nanoplatelets (GNP) nanofluid with specific surface area of 750 m 2 /g under laminar forced convection conditions inside a circular stainless steel tube subjected to constant wall heat flux. The analysis considers constant velocity flow and a concentration range from 0.025 wt.% to 0.1 wt.%. The impact of the dispersed nanoparticles concentration on thermal properties, convective heat transfer coefficient, thermal performance factor and entropy generation is investigated. An enhancement in thermal conductivity for GNP of between 12% and 28% is observed relative to the case without nanoparticles. The convective heat transfer coefficient for the GNP nanofluid is found to be up to 15% higher than for the base fluid. The heat transfer rate and thermal performance for 0.1 wt.% of GNP nanofluid is found to increase by a factor of up to 1.15. For constant velocity flow, frictional entropy generation increases and thermal entropy generation decreases with increasing nanoparticle concentration. But, the total entropy generation tends to decrease when nanoparticles are added at constant velocity and to decrease when velocity rises. Finally, it is demonstrated that a GNP nanofluid with a concentration between 0.075 wt.% and 0.1 wt.% is more energy efficient than for other concentrations. It appears that GNP nanofluids can function as working fluids in heat transfer applications and provide good alternatives to conventional working fluids in the thermal fluid systems.